2002
DOI: 10.1042/0264-6021:3630105
|View full text |Cite
|
Sign up to set email alerts
|

Major outer membrane proteins and proteolytic processing of RgpA and Kgp of Porphyromonas gingivalis W50

Abstract: Porphyromonas gingivalis is an anaerobic, asaccharolytic Gram-negative rod associated with chronic periodontitis. We have undertaken a proteomic study of the outer membrane of P. gingivalis strain W50 using two-dimensional gel electrophoresis and peptide mass fingerprinting. Proteins were identified by reference to the pre-release genomic sequence of P. gingivalis available from The Institute for Genomic Research. Out of 39 proteins identified, five were TonB-linked outer membrane receptors, ten others were pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
182
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(190 citation statements)
references
References 45 publications
7
182
1
Order By: Relevance
“…N-terminal sequencing of these proteins and the kgpЈ-ЈrgpB chimera gene product in the porT mutant produced no results, indicating a blocked N terminus, consistent with previous predictions that the pro domains of these proteins have N-terminal pyroglutamate (43).…”
Section: Discussionsupporting
confidence: 68%
“…N-terminal sequencing of these proteins and the kgpЈ-ЈrgpB chimera gene product in the porT mutant produced no results, indicating a blocked N terminus, consistent with previous predictions that the pro domains of these proteins have N-terminal pyroglutamate (43).…”
Section: Discussionsupporting
confidence: 68%
“…The pattern of protein bands obtained by SDS-PAGE analysis of the RgpA-Kgp complexes purified by Pike et al (1994) and Bhogal et al (1997) were the same as those obtained in this study with the Triton-wt complex, where PMF analysis confirmed the absence of the C-terminal domains of both RgpA and Kgp in the purified complex. Veith et al (2002) showed using 2D-PAGE analysis of P. gingivalis W50 outer membranes that the C-terminal domain of RgpA, RgpA A4 was present as a highly post-translationally modified form that reacted with mAb 1B5 whereas the other RgpA and Kgp domains obtained did not react with the mAb. This mAb has recently been reported to react with a phosphorylated branched mannan that has been suggested to be part of the outermost layer of the P. gingivalis cell wall (Paramonov et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal sequencing and PMF data shown in the present study demonstrate that the Kgp proteinase is involved in processing of the RgpA A3 adhesin domain and the majority of the RgpA and Kgp domains are processed by either the RgpA or RgpB proteinases. Using proteinase inhibitors to eliminate proteolytic processing during extraction, Veith et al (2002) showed that the RgpA and Kgp proteinase and adhesins are fully processed domains on the cell surface of P. gingivalis. Our data suggest that processed domains of the three polyproteins RgpA, Kgp and HagA combine noncovalently to form complexes either on the cell surface or immediately upon release from the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most of the prevalent T. forsythia glycoproteins identified in this study (the two S-layer glycoproteins TfsA (TF2261-2262) and TfsB (TF2663), TF2339, and its paralog TF1259) are located in the outer membrane of the bacterium, whereas the others (TF1056 and TF0091) are predicted lipoproteins. TF1259 and TF2339 exhibit C-terminal sequence similarity to the CTD family of P. gingivalis (51). TF1056 and TF0091 are predicted non-CTD lipoproteins, showing similarity to TonB-dependent receptor-associated proteins, which are generally known to be important for signal transmission to the cytoplasm and activation of target gene transcription (52).…”
Section: Discussionmentioning
confidence: 99%